Plan estratégico de gestión administrativa y comercial para el fortalecimiento de la competitividad de la microempresa "Ali Textiles" - Proaño, Kevin E. (2018)
The present research project consists of the design of a strategic administrative and commercial management plan to strengthen the competitiveness of the "ALY Textiles" company with the objective of improving and diversifying the different administrative and commercial processes, giving a benefit to development and commercially competitive growth of the organization. For the approach of the problem an analysis of the background of the company was made, taking into account the main factors that affect the organization, in order to solve it. In this way, the objectives and strategies for the realization of the plan were obtained. Analyzed aspects of the background and concepts on the strategic plans of institutional development and marketing that were previously executed.